PsycEXTRA Dataset 2005
DOI: 10.1037/e439492005-001
|View full text |Cite
|
Sign up to set email alerts
|

Use of Spirometry for Case Finding, Diagnosis, and Management of Chronic Obstructive Pulmonary Disease (COPD): Evidence Report/Technology Assessment, Number 121

Abstract: 3. Does the effectiveness of COPD-specific therapies to improve clinically relevant outcomes vary based on baseline severity or change in spirometry? 4. Is prediction of future COPD status based on spirometry, with or without clinical indicators, more accurate than prediction based on clinical indicators alone? Methods Articles published in the English language from 1966 to May 2005 were identified by searching MEDLINE ® and the Cochrane Database. Because the individual questions addressed different areas, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 286 publications
4
69
0
2
Order By: Relevance
“…24 However, on the basis of the results of the Agency for Heathcare Research and Quality evidence report and the recommendations of the US Preventive Services Task Force, most organizations no longer recommend this approach of universal screening. 23 We found that 762 (95%) of 800 patients recruited from a primary care setting who were not taking any respiratory medications, who scored 18 or less on the LFQ, and who had an FEV 1 /FVC ratio of less than 0.70 did not report a previous diagnosis of COPD. Thus, the LFQ, as a preliminary case-finding tool, may be an acceptable alternative to mass screening.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…24 However, on the basis of the results of the Agency for Heathcare Research and Quality evidence report and the recommendations of the US Preventive Services Task Force, most organizations no longer recommend this approach of universal screening. 23 We found that 762 (95%) of 800 patients recruited from a primary care setting who were not taking any respiratory medications, who scored 18 or less on the LFQ, and who had an FEV 1 /FVC ratio of less than 0.70 did not report a previous diagnosis of COPD. Thus, the LFQ, as a preliminary case-finding tool, may be an acceptable alternative to mass screening.…”
Section: Discussionmentioning
confidence: 94%
“…Given its high negative predictive value, the LFQ also has the potential to decrease the use of spirometry in asymptomatic patients and guide other diagnostic evaluations in symptomatic patients with spirometric evidence of obstructive lung disease. 22,23 Although our primary aim in the development of the LFQ was to identify patients who were candidates for further assessment using spirometry (and potentially to identify undiagnosed cases of COPD), a substantial number of abnormal spirometry measures (eg, FEV 1 <80% of predicted) were also identified using the LFQ. We based our a priori criteria for the success of the LFQ on its ability to detect airway obstruction, but its clinical utility may actually be much greater because of its potential also to detect clinically important restrictive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring lung function by spirometry to motivate smoking cessation has been a controversial topic because of conflicting data (Bize et al, 2009;Bohadana et al, 2005;Boushey et al, 2005;Enright & Crapo, 2000;Ferguson et al, 2000;Kotz et al, 2009;Mannino, 2006;McClure et al, 2009;Wilt et al, 2005;Young et al, 2010). Low FEV 1 is an independent risk factor for death from COPD and all causes as well as for lung cancer, cardiovascular disease, and stroke (Mannino et al, 2000;Young et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…25 For mild patients who remain undiagnosed, some argue that early detection and prevention -particularly in introducing smoking cessation programmes -may offer a better long-term prognosis 26,27 although other studies have not confirmed this. 28,29 Also, although only five European countries were represented in this analysis and there were some inter-country variations in demographic factors, the relationship between HRQL impairment and PCP-rated severity showed very similar patterns across countries, suggesting that these data may be representative at the European level. This requires confirmation in further studies, with representation in Northern and Eastern Europe.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%